Efektivitas Beberapa Ekstrak Tanaman sebagai Ovisida terhadap Aedes aegypti dalam Pencegahan Demam Berdarah Dengue - Linda Septiani; terza aflika happy; Risti Graharti; Femmy Andrifianie; Endah Setyaningrum (CV. Jasa Sukses Abadi, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health concern, with Aedes aegypti serving as the primary vector. The continuous use of synthetic insecticides has led to resistance development and environmental concerns, highlighting the need for safer and sustainable alternatives. This review aims to evaluate the ovicidal potential of selected plant extracts against Aedes aegypti as an early-stage vector control strategy. A literature review was conducted using relevant national and international publications focusing on plant-based ovicides. The findings indicate that extracts from Piper nigrum L., Ocimum basilicum, Syzygium myrtifolium Walp., Tithonia diversifolia, Acorus calamus L., Solanum lycopersicum, and Euphorbia hirta L. effectively reduce egg hatchability of Aedes aegypti. The ovicidal activity is associated with secondary metabolites such as flavonoids, alkaloids, saponins, tannins, terpenoids, polyphenols, and essential oils, which disrupt egg membranes and inhibit embryonic development in a concentration-dependent manner. These findings suggest that plant extracts possess promising potential as natural ovicides and may serve as a basis for further pharmaceutical development and formulation in sustainable dengue vector control.